2006
DOI: 10.1093/nar/gkl799
|View full text |Cite
|
Sign up to set email alerts
|

GO PaD: the Gene Ontology Partition Database

Abstract: Gene Ontology (GO) has been widely used to infer functional significance associated with sets of genes in order to automate discoveries within large-scale genetic studies. A level in GO's direct acyclic graph structure is often assumed to be indicative of its terms' specificities, although other work has suggested this assumption does not hold. Unfortunately, quantitative analysis of biological functions based on nodes at the same level (as is common in gene enrichment analysis tools) can lead to incorrect con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…A similar effect could occur if there are variations in coding practices within an institution, since a single diagnosis may be represented as several different ICD9 codes (which could get worse with usage of ICD-10). This is a limitation of LIMIT, which could be addressed if ICD9 codes were grouped, for example by using information theoretic approaches [45], into disease categories which have the same level of specificity.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect could occur if there are variations in coding practices within an institution, since a single diagnosis may be represented as several different ICD9 codes (which could get worse with usage of ICD-10). This is a limitation of LIMIT, which could be addressed if ICD9 codes were grouped, for example by using information theoretic approaches [45], into disease categories which have the same level of specificity.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of the former: any ontologically structured data point can be characterized with respect to information content (see e.g. Alterovitz et al, 2007, Lord et al, 2003a. Lord et al (2003b) found that this measure, in connection with sequence similarity, uncovered a number of genes in LocusLink that were manually mis-annotated (pp.…”
Section: Quantifying Quality Versus Quantifying Quantitymentioning
confidence: 99%
“…Assessment of GO's structure independent of annotation has tended to focus on issues of redundancy within the ontology structure; that is, using different names for the same concept or different concepts for the same name (Alterovitz et al, 2007;Onsongo et al, 2008). To the extent assessment of GO and its annotations are considered together, it is almost exclusively in the context of gene group enrichment analyses (Gross et al, 2012;Grossmann et al, 2007;Jantzen et al, 2011;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%